Natural enemies of the spiralling whitefiy, Aleurodicus dispersus Russell (Homoptera: Aleyrodidae): Parasitoids y depredators. - Blanco-Metzler, Belga (2016)
Composition of species of predators and parasitoid, as well as parasitoid abundance between banana farms associated with the spiraIling whitefIy, Aleurodicus dispersus Russell, were studied during 1997 and 1998 in Matina, Limltn, Costa Rica. Four parasitoids, Encarsiella noyesi Hayat, E. aleurodici (Girault), Encarsiella probo nsp. and Encarsia guadeloupae Viggiani were recovered from whitefIy nymphs. Two species of mite belonging to Phytoseiidae fami1y, Nephaspis sp. (Coleoptera: Coccinelidae), Scymnus sp. (Coleoptera: Coccinelidae), and three species of spiders: Plesiometa argyra (Araneida), Gasteracantha cancriformis (Araneida), and Chrysso sp. (Araneida), were the most common predators of whitefIy aduIt and nymphs. Percentage of parasitism betwecn farms was found to differ significantly being highcst in AGRODISA>SEMDEL> Anabel.